PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DANA OTONOMI KHUSUS DAN TINGKAT KEMISKINAN TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH DI KABUPATEN/KOTA PROVINSI ACEH - Machfud, Machfud; Asnawi, Asnawi; Naz'aina, Naz'aina (J-MIND (Jurnal Manajemen Indonesia), 2020)
ABSTRACT This study aims to examine the effect of Regional Original Revenue, Balancing Funds, Special Autonomy Funds, and poverty levels on the level of local financial independence. The research data used is a combination of cross section with time series in 23 regencies / cities in Aceh Province during 2013-2018, obtained from the Budget Realization Report (LRA) issued by the Directorate General of Fiscal Balance of the Ministry of Finance (DJPK Ministry of Finance). The data analysis method used is Panel Data Regression with the help of Eviews 9. The results of this study prove that the Regional Original Revenue has a positive and significant effect on the level of regional financial independence, while the balance funds and special autonomy funds have a negative and significant effect on the level of regional financial independence. The poverty does not significantly influence the level of regional financial independence. Keywords :  Regional Original Revenue, Balancing Fund, Special Autonomy Funds, Poverty Levels and Financial Independency Ratio